2021
DOI: 10.1108/prt-08-2021-0103
|View full text |Cite
|
Sign up to set email alerts
|

Rendering viscose fabric dye-able with anionic dyes using plasma treatment technique and chitosan nanoparticles as an eco-friendly approach

Abstract: Purpose This paper aims at studying the oxygen plasma treatment and the previously prepared and fully characterized chitosan nanoparticles (CNPs) as a green and eco-friendly strategy for surface modification of viscose fabric. This was done to render viscose fabric dye able with two types of acid dyes that do not have direct affinity to fix on it via improving the fabric wettability. Design/methodology/approach To achieve the goal, viscose fabric was activated with oxygen plasma at optimum conditions and coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Due to ionic bombardment, the part with less bonding energy and atoms close to it was removed from the surface. Therefore, crackling and etching can reduce the weight and degree of whiteness of the sample (Mostafa, 2022b; Kan, 2014). This is in accordance with other studies that showed the nitrogen plasma treatments reduce the weight in cotton fibers between 1%–6% (Bhat et al , 2011; Bhat et al , 2011) and 0.5% (Nithya et al , 2011), while in case of gray cotton fabrics; the loss ranged between 1.5 and 4% (Wang et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to ionic bombardment, the part with less bonding energy and atoms close to it was removed from the surface. Therefore, crackling and etching can reduce the weight and degree of whiteness of the sample (Mostafa, 2022b; Kan, 2014). This is in accordance with other studies that showed the nitrogen plasma treatments reduce the weight in cotton fibers between 1%–6% (Bhat et al , 2011; Bhat et al , 2011) and 0.5% (Nithya et al , 2011), while in case of gray cotton fabrics; the loss ranged between 1.5 and 4% (Wang et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This is because no hazardous chemicals or poisonous solvents are exploited in the treatment of cotton fabric using nitrogen gas plasma. In this study, and based on our laboratory trials with our colleagues in addition to our recent published works (Mostafa, 2022b), cotton fabrics are activated by the optimum plasma conditions used during the process: the discharged gas pressure, 200 m torr; discharge power, 30 W; and duration, 60 min. The resultant nitrogen plasma-treated fabrics are dyed with different concentration of Acid Blue 284 and the effects of each treatment on color strength (K/S), fastness properties to light, rubbing and perspiration and durability as well as tensile strength, elongation at break, wettability, zeta potential and degree of whiteness of the treated samples were determined and compared with untreated fabric.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation